Comparative Evaluation of Potentially Radiolucent Projectile Components by Radiographs and Computed Tomography1. Issue 6 (27th October 2016) - Miller, Catherine R.; Haag, Michael; Gerrard, Chandra; Hatch, Gary M.; Elifritz, Jamie; Simmons, Michael C.; Lathrop, Sarah; Nolte, Kurt B.
Abstract: Projectile components that are traditionally radiolucent can be of considerable importance in determination of weapon type and caliber, but they are often missed on evaluation of postmortem radiographs. We hypothesized that these components would be significantly better visualized by evaluation of computed tomography (CT) scans compared to the practice standard of radiography alone. In this project, potentially radiolucent projectile components were both pulled apart and fired, and the radiolucent components were recovered. These components were embedded in blocks of ballistics gelatin and were imaged using both radiography and CT. The scans were evaluated by three blinded, board‐certified radiologists for the presence/absence of projectile components and true‐negative regions in each block. If a radiologist indicated visualization of a projectile component, they were further requested to describe their observation. It was found that traditionally radiolucent projectile components are not significantly more often identified on CT scans than radiography ( p  <   0.05).